Scanning electrochemical microscopy - Bard, Allen J.; Mirkin, Michael V., 1961- (CRC Press, 2012)
"Scanning Electrochemical Microscopy (SECM) is an indispensable tool for the study of surface reactivity, and scientists are increasingly attracted to this method because of its simplicity of use and the quantitative results. The fast expansion of the SECM field during the last several years has been fueled by the introduction of new probes, commercially available instrumentation, and new practical applications. This book offers essential background and in-depth overviews of specific applications. This edition, thoroughly updated, retains original chapters and offers four new chapters covering applications that have emerged or expanded since the first edition's publication." --